Three-dimensional in vivo evaluation of the cornea in patients with unilateral posterior interstitial keratitis - Gu, Shao-Feng; Gao, Shuang; Wang, Hai-Kun; He, Lin-Hui; Peng, Rong-Mei; Xiao, Ge-Ge; Hong, Jing (Frontiers in Medicine, 2023)
The purpose of this study was to investigate the in vivo morphologic features of the cornea in patients with unilateral posterior interstitial keratitis. Methods: Seven eyes of 7 patients with unilateral posterior interstitial keratitis were examined by slitlamp biomicroscopy, anterior segment optical coherence tomography (AS-OCT), and in vivo confocal microscopy (IVCM). The imaging features of the cornea were evaluated and analyzed. Results: By slit-lamp examination, the posterior corneal stromal opacities were observed in all 7 eyes, and deep neovascularization in 4 eyes. The posterior stromal opacities showed higher reflectivity with an intact overlying epithelium by AS-OCT and did not invade the Bowman's layer in all cases. IVCM revealed highly reflective dispersed microdots, needle-shaped bodies, and increased reflectivity of keratocytes in the lesion site in all patients. Active Langerhans cells and an attenuated subbasal nerve plexus were observed in 5 eyes. After treatment, the active Langerhans cells disappeared; however, highly reflective microdots and needle-shaped bodies remained. Conclusion: The three-dimensional evaluation of slit-lamp biomicroscopy, AS-OCT, and IVCM may help in the early diagnosis of patients with posterior interstitial keratitis.